Testing the Hybrid Battery Approach to Evaluating Sports-Related Concussion in the National Hockey League: A Factor Analytic Study. (26th July 2019) - Echemendia, R J; Bruce, J M; Thelen, J; Hutchison, M; Comper, P; Meeuwisse, W
Abstract: Purpose: Traditional "paper and pencil" neuropsychological tests and computerized test batteries have been employed in the assessment of sports-related concussion (SRC). Each type of test has inherent strengths and weaknesses. The NHL has constructed a "hybrid" battery of tests that uses both traditional and computerized measures in the evaluation of its players suspected of SRC. The purpose of this paper is to use factor analytic techniques to examine the relationships among the measures that comprise this battery. Methods: Post-injury neuropsychological test data using the hybrid battery were obtained from 343 NHL players following their first concussion while playing in the league. ImPACT was used as the computer test battery. The traditional battery included: Hopkins Verbal Learning Test, Brief Visuospatial Memory Test, Color Trails, PSU Cancellation, Symbol Digits Modalities Test (including incidental memory), and Verbal Fluency. Results: Five factors were extracted explaining 64.55% of the variance. The factor labels and the measures principally loading on each factor were as follows: Factor 1, Verbal Learning and Memory (HVLT Total and Delayed Recall); Factor 2, Processing Speed (Color Trails A/B, PSU Cancellation, and SDMT-Total); Factor 3, Visual Memory (BVMT- Total and Delayed); Factor 4, Cued Memory (ImPACT-Visual and Verbal Memory Composites); and Factor 5, Reaction Time (ImPACT Reaction Time and Visual Motor Speed composites). Conclusion: These data underscore the unique contributions of traditional and ImPACT neuropsychological measures to the evaluation SRC in a sample of professional hockey players. It appears that both approaches measure different aspects of cognitive functioning. The next logical step is to use these data in evaluating the diagnostic utility of these measures as part of a combined battery.